Abstract 4494: MPT0G066, a novel microtubule-destabilizing agent, induces cell apoptosis and potentiates antineoplastic effects of cisplatin in human ovarian cancer cells in vitro and in vivo . - Chun-Han Chen; Ya-Chi Li; Li-Hsun Chang; Jing-Ping Liou; Shiow-Lin Pan; Che-Ming Teng (Cancer Research, 2013)
Abstract Ovarian cancer is one of the leading causes of death in women with gynecological malignancy in the United States. About 70% of ovarian cancer cases are diagnosed at an advanced stage resulting in poor survival rate. In the present study, we provide the data showing that MPT0G066, a novel synthetic arylsulfonamide compound, inhibited cell growth and viability in human ovarian cancer cell lines as evidenced by sulphorodamine B (SRB) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. Cell cycle distribution was also determined by flow cytometry, the data revealed that MPT0G066 induced cell cycle arrest at multipolyploidy (MP) phase (SKOV3 cells) or at G2/M phase (A2780 cells) in 24 hours and ultimately increased the cell population in sub-G1 phase in 48 hours. Moreover, in vitro tubulin polymerization assay, in situ labeling of β-tubulin and western blot analysis showed that MPT0G066, similar to colchicine and vincristine, promoted tubulin depolymerization and altered the expression of G2/M cell cycle regulatory proteins. Mechanistically, MPT0G066 induced JNK activation and altered Bcl-2 family proteins by increasing the expression of p-Bcl-2, Bax, Bim, Puma and decreasing the level of Bcl-2 and Mcl-1. Disruption of mitochondrial proteins triggered intrinsic apoptotic pathways through the cleavage of caspase-3, -7, -9, and poly (ADP-ribose) polymerase (PARP). Moreover, treatment with SP600125, a JNK inhibitor, abolished the effects of MPT0G066 on cell viability, Bcl-2 family proteins and apoptotic cell death. Finally, we used xenograft mouse model to demonstrate that MPT0G066 is able to suppress the growth of ovarian carcinoma A2780 cells and potentiated the antineoplastic effects of cisplatin in vivo. Immunohistochemistry data also confirmed MPT0G066-induced JNK activation in tumor sections. In summary, these results suggested that MPT0G066 could disrupt microtubule dynamics, and lead to cell cycle arrest at MP phase or G2/M phase. MPT0G066 induced JNK activation and altered Bcl-2 family proteins, which ultimately caused apoptosis through the intrinsic apoptotic pathways. These finding indicated that MPT0G066 is a potential anticancer agent worthy for further development and may foster novel treatment for patients with ovarian cancer. Citation Format: Chun-Han Chen, Ya-Chi Li, Li-Hsun Chang, Jing-Ping Liou, Shiow-Lin Pan, Che-Ming Teng. MPT0G066, a novel microtubule-destabilizing agent, induces cell apoptosis and potentiates antineoplastic effects of cisplatin in human ovarian cancer cells in vitro and in vivo. [abstract]. In: Proceedings of the 104th Annual Meeting of the American Association for Cancer Research; 2013 Apr 6-10; Washington, DC. Philadelphia (PA): AACR; Cancer Res 2013;73(8 Suppl):Abstract nr 4494. doi:10.1158/1538-7445.AM2013-4494